NILAI-NILAI BUDAYA MINANGKABAU DALAM KUMPULAN CERITA PENDEK ‘CARITO ETEK SIAR - INDAK TAU DIATAH TAKUNYAH’ KARYA ADRIYETI AMIR - TRISNA, AMELIA; Abdurahman, Abdurahman; Hamidin, Hamidin (Jurnal Bahasa dan Sastra, 2014)
The purpose of this study is to describe the values of Minangkabau culture in a collection of short stories 'Carito Etek Siar-Indak Tau Diatah Takunyah' Amir Adriyeti work. Study of the theory in this study, namely: (1) the nature of literature, (2) the nature and elements of the short story, (3) literary analysis approach, (4) the nature and cultural values. This research is qualitative research with descriptive method. The data in this study are the values of Minangkabau culture in a collection of short stories 'Carito Etek Siar- Indak tau Diatah Takunyah' Amir Adriyeti work. Data source is a collection of short stories 'Carito Etek Siar-Indak Tau Diatah Takunyah' Amir Adriyeti work. The sections relating to research data were analyzed by means of reading, understand, appreciate, identify, and noting how cultural values contained in a collection of short stories. Data was collected by means of read carefully the short story collection 'Carito Etek Siar-Indak Tau Diatah Takunyah' Amir Adriyeti work, in order to get an overall understanding of the content of the story, marking the structure section contains the description of the values of Minangkabau culture in it , identifying cultural values contained in a collection of short stories 'Carito Etek Siar- Indak Tau Diatah Takunyah' Amir Adriyeti work. Data analysis techniques, an inventory of data, translating data into Indonesian, classifies data based on the problems presented in this study, the data that have been classified and analyzed based on the theory that has been described, after the data were analyzed, do inference. After analysis, it was found Minangkabau cultural values contained in a collection of short stories 'Carito Etek Siar-Indak Tau Diatah Takunyah' Amir Adriyeti work. Minangkabau cultural values consists of values of 6 pieces of religious systems, the values of kinship in Minangkabau society 4 pieces, and the values of livelihood system 5 pieces.